2014
DOI: 10.1111/apha.12397
|View full text |Cite
|
Sign up to set email alerts
|

ET‐1 increases reactive oxygen species following hypoxia and high‐salt diet in the mouse glomerulus

Abstract: Aim The current study was designed to determine whether ET-1 derived from endothelial cells contributes to oxidative stress in the glomerulus of mice subjected to a high salt diet and/or hypoxia. Methods C57BL6/J control mice or vascular endothelial cell ET-1 knockout (VEET KO) mice were subjected to three-hour exposure to hypoxia (8% O2) and or 2 weeks of high salt diet (4% NaCl) prior to metabolic cage assessment of renal function and isolation of glomeruli for determination of reactive oxygen species (ROS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 26 publications
0
30
0
Order By: Relevance
“…Circulating levels of ET-1 are elevated in diabetes [28], which may be due to either increased ET-1 production or reduced clearance. Furthermore, it was recently demonstrated that ET-1, via ETA-Rs, increases the glomerular production of reactive oxygen species and urinary protein leakage during exposure to hypoxia in mice fed a highsalt diet [29]. Thus, ET-1 signalling via ETA-Rs may play an important role in the development of diabetic nephropathy, especially considering the intrarenal hypoxia that develops soon after the onset of diabetes [30].…”
Section: Discussionmentioning
confidence: 99%
“…Circulating levels of ET-1 are elevated in diabetes [28], which may be due to either increased ET-1 production or reduced clearance. Furthermore, it was recently demonstrated that ET-1, via ETA-Rs, increases the glomerular production of reactive oxygen species and urinary protein leakage during exposure to hypoxia in mice fed a highsalt diet [29]. Thus, ET-1 signalling via ETA-Rs may play an important role in the development of diabetic nephropathy, especially considering the intrarenal hypoxia that develops soon after the onset of diabetes [30].…”
Section: Discussionmentioning
confidence: 99%
“…The glomeruli were isolated from rat kidney cortex as described (Heimlich et al, 2014). Glomeruli were homogenized in a Dounce homogenizer in RIPA buffer (consisting of 0.1% sodium dodecyl sulfate, 1% NP-40, 150 mM NaCl, 1% sodium deoxycholate and 10 mM ethylenediaminetetraacetic acid in 25 mM Tris-HCl (pH 7.2) and then centrifuged ( 12,000g, 4°C) for 20 min.…”
Section: Western Blot Analysismentioning
confidence: 99%
“…To (38), and stimulates glomerular formation of reactive oxygen species in response to highsalt diet or hypoxia (15).…”
Section: Genetic Rodent Models: Et-1/et a Pathway Versus Et-1/ Et B Pmentioning
confidence: 99%